Ultrasound treatment enhances tomato drought resistance from germination to seedling stage - Nogueira, António; Teixeira, António; Martins, Joana; Gerós, Hernâni; Puga, Hélder (Frontiers in Plant Science, 2026)
Drought stress poses a major threat to tomato seed germination and early seedling growth. These critical stages for the establishment of a successful crop are compromised by drought, which disrupts water uptake, impairs metabolic functions, and induces oxidative damage. As a cornerstone of global agriculture, tomato (Solanum lycopersicum) is increasingly vulnerable to these environmental pressures during its early development stages. With climate change amplifying the frequency and intensity of droughts, these challenges are growing, thereby threatening agricultural productivity worldwide. This study investigates the efficacy of ultrasound-assisted seed treatment as a novel strategy to mitigate drought effects, using osmotic stress induced by D-mannitol (ranging from 0 to –0.75 MPa). Tomato seeds were treated with multifrequency and multimode ultrasound technology (19.8 kHz, 200 W, 7.5 min) and evaluated for germination, seedling vigor, and biochemical responses under controlled conditions. Results demonstrate that ultrasound significantly enhances the germination percentage (up to 34% at –0.75 MPa) and seedling emergence (up to 36% at –0.50 MPa), while reducing germination time by up to 17% under high osmotic stress (–0.50 and –0.75 MPa). Moreover, ultrasound significantly increased the seedling vigor index I and chlorophyll content (up to 50% at −0.50 MPa). Superoxide dismutase and catalase activity in seeds increased by up to 45% and 77%, respectively, with similar values observed in seedlings. Total antioxidant activity (DPPH, ABTS, FRAP) increased in seeds and seedlings by up to 70% (under all conditions). Ultrasound-treated seeds exhibited elevated malondialdehyde (MDA) levels (up to 31% at –0.75 MPa), indicating an initial mechanical stress, while the resulting seedlings showed a reduction of MDA in all conditions (up to 48%), suggesting enhanced membrane stability over time. Principal component analysis and correlation analysis revealed distinct physiological and biochemical trait variations, with ultrasound effects more pronounced in seedlings. These findings highlight ultrasound’s potential to activate adaptive mechanisms, counteracting drought-induced oxidative damage and improving early plant performance. This scalable, eco-friendly technique offers a promising alternative to conventional priming methods.